Effect of classroom acoustics on the speech intelligibility of students - Alessandra Terra Vasconcelos Rabelo; Juliana Nunes Santos; Rafaella Cristina Oliveira; Max de Castro Magalhães (CoDAS)
Purpose:To analyze the acoustic parameters of classrooms and the relationship among equivalent sound pressure level (Leq), reverberation time (T30), the Speech Transmission Index (STI), and the performance of students in speech intelligibility testing.Methods:A cross-sectional descriptive study, which analyzed the acoustic performance of 18 classrooms in 9 public schools in Belo Horizonte, Minas Gerais, Brazil, was conducted. The following acoustic parameters were measured: Leq, T30, and the STI. In the schools evaluated, a speech intelligibility test was performed on 273 students, 45.4% of whom were boys, with an average age of 9.4 years. The results of the speech intelligibility test were compared to the values of the acoustic parameters with the help of Student's t-test.Results:The Leq, T30, and STI tests were conducted in empty and furnished classrooms. Children showed better results in speech intelligibility tests conducted in classrooms with less noise, a lower T30, and greater STI values. The majority of classrooms did not meet the recommended regulatory standards for good acoustic performance.Conclusion:Acoustic parameters have a direct effect on the speech intelligibility of students. Noise contributes to a decrease in their understanding of information presented orally, which can lead to negative consequences in their education and their social integration as future professionals.